Politeness in Balinese and English - I Gede Wayan Suparna (Universitas Pendidikan Ganesha, 2012)
The aims of this study are to find the similarities and differences of politeness in Balinese and English. Based on the discussion there are some similarities and also differences between Balinese and English. Balinese language is used mostly in Bali Island. It has the same characteristics with Javanese language. It is used in daily conversation and adat (social organization in Bali) meeting among Balinese people. Balinese people are popular for being polite, friendly, and helpful. They have principles of menyama braya (cooperative), asah, asih, asuh (understanding), ngendepang raga (good manners) in getting along with other people. Balinese speech varies depending on social context, using three levels of language called alus sor, alus madya and alus singgih. When one is speaking, he/she has to apply the principles of “nganutin catur wangsa” (using certain level of language based on his/her status of being superior or inferior) and ngendepang raga (good manners).